PENGARUH MOBILE HEALTH E-SERVICE QUALITY PADA KEPUASAN PELANGGAN DAN KEPERCAYAAN PELANGGAN SERTA KELANJUTAN PENGGUNAANNYA DI ERA PANDEMIK COVID-19 - Ripka Renaldi; Christabella Monica; Paul Lumbantobing (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Health application has rapidly gained its popularity since the COVID-19 pandemicstroke the world. Looking at its promising future in function and variousadvantages, we conducted a study to observe the effect of e-service quality oncustomer satisfaction, customer trust, and subsequently customer retention. Thisstudy uses quantitative method, the population is users of mobile healthapplications who are of productive age. The sampling technique used is simplerandom sampling with the criteria of respondents who have used the mHealthapplication as many as 149 respondents. From the results of our study, it was foundthat e-service quality has a positive relationship with customer satisfaction andtrust, customer satisfaction and trust have a positive relationship with customerretention. However, e-service quality does not have a direct relationship withcustomer retention. This may be influenced by application factors that often crashor user doubts about their privacy when providing information in applications, aswell as comparisons between applications in terms of price and quality of service.